Precambriam Organic Compounds from the Ketilidian of South-West Greenland, Part III. - Raunsgaard Pedersen, K.; Lam, Jørgen (Meddelelser om Grønland, 1970)
Ketilidian sedimentary rocks nearly 2000 m.y . old and only slightly metamorphosed have been shown to contain fossils and organic compounds. Results of work on organic material from a 1-3 m thick coal-graphite layer from the Foselv Formation in the Sortis Group in Grænseland are presented. Aliphatic (straight chain, branched and cyclic) hydrocarbons are dominant in the extract from two coal-graphite samples weighing about 4 kg and 10 kg respectively. Further investigations of these compounds have revealed many saturated straight-chain hydrocarbons, with the n-C15 alkane, the most abundant among the normal alkanes, ranging from C12 to about C21 , and various isoalkanes and anteisoalkanes. Saturated cyclic hydrocarbons like alkyl cyclohexanes, and homologous series of alkyl benzenes and alkyl naphthalenes are also present. A series of monoterpenoid compounds is present. Six of them are fairly well characterized by their mass spectra. Fatty acids and methyl esters of fatty acids are present, notably a homologous series of straight-chain fatty acids. Branched acids are also present in minor amounts. The organic compounds further indicate that this Precambrian coal-graphite layer is the result of biological activity.